Factors associated with low-level physical activity in elderly patients with chronic obstructive pulmonary disease - Lee, Sang Hee; Kim, Ki Uk; Lee, Haejung; Kim, Yun Seong; Lee, Min Ki; Park, Hye-Kyung (The Korean journal of internal medicine, 2018)
In patients with chronic obstructive pulmonary disease (COPD), the extent of physical activity (PA) is correlated with disease severity and prognosis. However, factors associated with low-level PA in elderly COPD patients are not known. We assessed the levels of PA and clinical factors associated with low-level of PA in elderly COPD patients. This was a secondary analysis of a multicenter, prospective study of 245 patients with COPD. Among them, 160 patients with 65 years or more were included. Three PA groups were defined with respect to daily activity time (low, moderate, and high). Health related quality of life (HRQL) was measured using St. George's respiratory questionnaire (SGRQ) and 36-item short-form health survey. Anxiety and depression status were assessed employing the hospital anxiety and depression scale (HADS). Multivariate logistic regression was performed to identify independent predictors of low-level PA in elderly COPD patients. Of all the 160 patients, 103 (64.4%) engaged in low-level PA. Upon univariate analysis, a decreased exercise capacity (6-minute walk test < 250 m), an increased dyspnea (the modified medical research council [MMRC] dyspnea scale ≥ 2), a decreased HRQL (total SGRQ score), and a presence of depression (HADS-D ≥ 8) were significantly associated with low-level PA. Upon multivariate analysis, an MMRC grade ≥ 2 (hazard ratio [HR], 2.550; = 0.034), and HADS-D ≥ 8 (HR, 2.076; = 0.045) were independently associated with low-level PA in elderly COPD patients. Two-thirds of elderly patients with COPD reported low-level of PA. More severe dyspnea and a presence of depression were independently associated with low-level PA in elderly COPD patients.